How Demographics and General Economic Mood Affect Investor Risk Tolerance? - Restana, Median Dwi; Komalasari, Puput Tri (Southeast Asian Business Review, 2023)
Investment decisions made "‹"‹by investors are strongly influenced by their risk tolerance. Individual risk tolerance will influence their asset allocation decision. This paper used primary data to examine the factors influencing investor risk tolerance. Two factors considered in this study are demographics and general economic mood. Demographic characteristics include gender, occupation, age, marital status, income, and education. General economic mood is people's perceptions about the prospects for a country's economy at present and in the future. Using convenience sampling, we distributed questionnaires to investors in the Indonesia Stock Exchange and senior students. The total number of data used in this research is 200 respondents. This research found that the general economic mood, gender, and occupation positively impact investor risk tolerance. In contrast, our research found the negative impact of education and average monthly income on investors' risk tolerance. Further, age and marital status do not affect the investor's risk tolerance. This finding is important for financial planners to advise on personal investment decisions.